IMPLEMENTATION OF CHARACTER EDUCATION UNDERSTANDING TO CHILDREN BY PARENTS - Sugiarti, Rini -; I.Winta, Mulya Virgonita; Erlangga, Erwin (Universitas Semarang, 2021)
Child character, formed early. Factors that greatly influence character building in children include parental care. As is known, there is a picture that changes in biological, psychological and social aspects including children's behavior are the basic development of children that come from reciprocal interactions with the social environment, including family, school and various elements therein, as well as friends / peers. Therefore, the development and formation of children's character is influenced by various contexts around them. This context comes from interactions with parents as part of the family, neighbors, school, classmates, playmates, and various other important settings. The purpose of this activity is to provide understanding for parents to be able to implement character education in children, in terms of cognitive, personality, religious spirituality, which will be seen in children's behavior. Participants in the activity were the Semarang City Women and Children Protection Network (JPPA) activists under the Semarang City Women Empowerment and Child Protection Service (DP3A), with a total of 456 participants. Methods of activities carried out by using lectures, exercises and discussions as well as pre-tests and post-tests are used to evaluate the effectiveness of the implementation of activities. The results of this service show an increase in understanding among parents regarding the implementation of understanding character education for children in the family.